Oviposition Behavior of Indianmeal Moths With and Without Synthetic Pheromone - Idell, Amanda; Gerken, Alison (My University, 2018)
Plodia interpunctella, commonly known as the Indianmeal moth, is a pyralid moth that is a pest of stored food products (Mohandrass, 2007). While there are many known factors that influence oviposition, like food odor and type of food available (Mohandrass, 2007), the effect of extra sex pheromones is not known. We tested progeny output to see if femaleP. interpunctella will produce less progeny when there is a large dose of synthetic pheromone in the environment. Our research did not show any significant difference between the females exposed to the pheromone and those that were not exposed, in both the total number of progeny produced and weight of the progeny. This experiment is important due to the quantity of pheromone-baited traps that are a major part of pest management for P. interpunctella (Mullen, 1998). This suggests that the widespread use of this pheromone to attract and trap male P. interpunctella does not also have an additional effect on females, which would have been a hidden benefit of this method of trapping and pest control.
Keywords: Fall 2018